Influence of Digital Play on Alphabet Recognition: Evaluating Technology-Based Games in Preschool Literacy - Crescencio, Riza M.; Pinili, Lilibeth; Opingo, Kaitlin Marie; Revalde, Helen (International Journal of Educational Studies, 2025)
This study investigated the effectiveness of traditional instruction and technology-based games in improving the alphabet knowledge of preschool learners at Panaghiusa Elementary School and San Roque Elementary School. Using a quasi-experimental design, 60 purposively selected learners were divided into two groups: a control group that received teacher-led lessons and an experimental group that used interactive educational applications, Kids Academy and Starfall. Pretest and posttest assessments measured uppercase recognition, lowercase recognition, and producing letter sounds. Results showed significant improvements in both groups, with the control group achieving higher mean gains, indicating the strong effect of structured traditional teaching. However, the experimental group also reached mastery, demonstrating that technology-based games are effective in reinforcing and sustaining alphabet knowledge while engaging learners. These findings highlight the value of combining traditional instruction with interactive digital tools to create a balanced approach for strengthening early literacy skills. The study provides practical insights for educators, curriculum planners, and policymakers in designing effective preschool literacy programs.